Mammalian display screening of diverse cystine-dense peptides for difficult to drug targets. Issue 1 (December 2017) - Crook, Zachary; Sevilla, Gregory; Friend, Della; Brusniak, Mi-Youn; Bandaranayake, Ashok; Clarke, Midori; Gewe, Mesfin; Mhyre, Andrew; Baker, David; Strong, Roland; Bradley, Philip; Olson, James
Abstract Protein:protein interactions are among the most difficult to treat molecular mechanisms of disease pathology. Cystine-dense peptides have the potential to disrupt such interactions, and are used in drug-like roles by every clade of life, but their study has been hampered by a reputation for being difficult to produce, owing to their complex disulfide connectivity. Here we describe a platform for identifying target-binding cystine-dense peptides using mammalian surface display, capable of interrogating high quality and diverse scaffold libraries with verifiable folding and stability. We demonstrate the platform's capabilities by identifying a cystine-dense peptide capable of inhibiting the YAP:TEAD interaction at the heart of the oncogenic Hippo pathway, and possessing the potency and stability necessary for consideration as a drug development candidate. This platform provides the opportunity to screen cystine-dense peptides with drug-like qualities against targets that are implicated for the treatment of diseases, but are poorly suited for conventional approaches. Pathologies related to protein:protein interaction are hard to treat but cystine-dense peptides have the potential to disrupt such interactions. Here the authors develop a high-diversity mammalian cell screen for cystine-dense peptides with drug potential and use it to identify a YAP:TEAD inhibitor.